The assessment of ubiquitin E3 ligase activity of RNF4 on ALS-related NEK1 protein - Canaslan, Sezgi (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Amyotropic lateral sclerosis (ALS) is a serious and progressive motor-neuron disease in which neurons that control voluntary muscles gradually deteriorate. Patients lose the ability to speak, move and breathe. To date, 30 ALS associated genes have been discovered. The products of mutated genes generally follow the similar pattern which is protein aggregation. In 2014, the results of the global MinE project have announced that NEK1 is a new ALS-related gene. NEK1 is a serine/threonine kinase functioning in cell cycle regulation, DNA damage response, cilia formation, etc. However, its contribution to disease phenotype is still not known. If NEK1 shares the same characteristic with other ALS-related proteins, it tends to aggregate. These aggregates can be cleared with the help of ubiquitin-proteasome system. In this study, we investigated whether NEK1 is a new target for RNF4 which is a special ubiquitin E3 ligase. If RNF4 is an E3 ligase for NEK1, it may affect the stability of NEK1 leading to its degradation by the proteasome. In silico anaylsis and co-immunoprecipitation experiments have suggested that NEK1 and RNF4 physically interact. RNF4 overexpression changes the stability of NEK1. In addition, the silencing of RNF4 with siRNA causes also the stabilization of NEK1. We have analyzed the ubiquitination of wild type NEK1 and one of its the disease-related versions, tNEK1. According to our preliminary results, NEK1 is ubiquitinated and tNEK is hyperubiquitinated. In conclusion, our study shows that NEK1 can be a new substrate of RNF4 and RNF4 can lead to further ubiquitination of NEK1 and tNEK1. These findings can contribute to improvements in therapeutic interventions for still incurable ALS.
Keywords: Amyotrophic lateral sclerosis.